2022
DOI: 10.1111/1556-4029.15165
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crime scene contaminants on surface‐enhanced Raman analysis of hair

Abstract: Forensic analysis of hair is important as hair is one of the most commonly examined forms of trace evidence found at crime scenes. A growing body of evidence suggests that surface‐enhanced Raman spectroscopy (SERS), a label‐free and non‐destructive analytical technique, can be used to detect and identify artificial colorants present on hair. However, hair collected at crime scenes is often contaminated by substances of biological and non‐biological origin present at such locations. In this study, we investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Once the contaminant was removed, SERS could be used to detect and identify hair colourants. 16 In the current study, we investigate the extent to which this simple washing procedure could be used to remove the discussed above contaminants from hair. We found that SERS spectra acquired from cleaned SpBlu-colored hair spectra were nearly identical to the spectra acquired from uncontaminated hair (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the contaminant was removed, SERS could be used to detect and identify hair colourants. 16 In the current study, we investigate the extent to which this simple washing procedure could be used to remove the discussed above contaminants from hair. We found that SERS spectra acquired from cleaned SpBlu-colored hair spectra were nearly identical to the spectra acquired from uncontaminated hair (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Kurouski group showed in 2022 that the ability to detect colourants on contaminated hair varies from contaminant to contaminant. 16 Some contaminants such as saliva and dirt did not block the underlying Raman signal, while others such as blood did. Some contaminants, like bleach, destroyed the possibility of detecting the underlying colourant even after the hair was rinsed.…”
Section: Introductionmentioning
confidence: 99%
“…However, no statistically signicant accuracy was found in classication of spectra acquired from fabric contaminated In our previous study, we demonstrated that some household contaminants could obscure the readability of SERS-based identication of dye content on hair. 32 However, the gentle removal of such contaminants by water allowed for restoration of the accuracy of SERS-based sensing of dyes. One can expect that a similar approach could be used to remove paint from the colored fabric.…”
Section: Classmentioning
confidence: 99%
“…Surface-enhanced Raman spectroscopy (SERS) is a versatile tool for analyzing and detecting molecular species and has been employed in a wide variety of applications, including molecular imaging of live cells, homeland security, , criminal investigations, , environmental analysis, , food safety, , and even anti-counterfeiting. , To collect high-intensity Raman signals from analyte molecules in SERS, enhanced localized electromagnetic fields on the substrate and/or energetically effective charge-transfer processes between the substrate material and analyte molecules should be realized . Among these enhancement mechanisms, electromagnetic field enhancement, which is also called the electromagnetic (EM) mechanism, provides the largest contribution to Raman signal enhancements.…”
Section: Introductionmentioning
confidence: 99%